Rationalism in Philosophical Studies - Afifah, Umi (Yayasan Sembilan Pemuda Indonesia, 2023)
This article discusses rationalism which is reviewed from various scopes starting from Rationalism Figures such as, Rece Descartes (1596-1650), Baruch De Spinoza (1632-1677), Leibniz (1646-1716), Icholas Malerbranche (1638-1775), Harun Nasution, and the philosophical views of racialism towards humas, science, education, and towards curriculum (implementation in the field). Rationalism is a philosophical teaching that holds that reason, or reason, is the most important tool for acquiring and testing knowledge. Rationalism, reason is the main source of knowledge. Theoretically, he contradicts empiricism by refusing to consider the five senses as a source of knowledge. Belief that reasons has the power and authority to reveal knowledge and truth. According to rationalism, humans’ ability to seek and respond to truth is based on their natural intellectual abilities.